ANALISIS PERBANDINGAN KINERJA KEUANGAN DAN HUBUNGANNYA DENGAN HARGA PASAR SAHAM PADA PT. CIPUTRA DEVELOMPENT Tbk. DAN PT LIPPO KARAWACI Tbk. PERIODE 2001-2005 - Edward Edward (Business Management Journal, 2017)
Financial report is an important tool for the user to appraise company performance. In company’s financial report we usually use some ratios; those ratios are liquidity ratio, leverage ratio, activity ratio, and profitability ratio. Beside those financial ratios, in this research the journalist added Z-score analysis to find out bankruptcy possibility. Higher Z-Scores has shown us the lower bankruptcy possibilty.The writers choose PT Ciputra Development Tbk. and PT Lippo Karawaci Tbk. to observe because both companies have a lot of experience in property industry. From the research, we found out that PT Lippo Karawaci has a better financial ratio and Z-Scores than PT. Ciputra Development Tbk. and for the company, the result of the research could be important input to company’s strategic planning. Keyword : Financial Report, financial ratios, Z-Scores